2013
DOI: 10.1088/0953-8984/26/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the twofold surface of the icosahedral Ag–In–Yb quasicrystal

Abstract: The structure of the twofold surface of the icosahedral (i-)Ag-In-Yb quasicrystal has been investigated using low energy electron diffraction (LEED) and scanning tunneling microscopy (STM). The LEED confirms that the surface exhibits quasicrystalline long range order with the twofold rotational symmetry expected from the bulk. STM images reveal a step-terrace structure with terrace size comparable to that of the other high symmetry surfaces of the same quasicrystal. The distribution of step heights and high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…This viewpoint is consistent with the latest reports on the surface structure study of i-Ag-In-Yb. [52][53][54]…”
Section: I-ag-in-ybmentioning
confidence: 99%
See 1 more Smart Citation
“…This viewpoint is consistent with the latest reports on the surface structure study of i-Ag-In-Yb. [52][53][54]…”
Section: I-ag-in-ybmentioning
confidence: 99%
“…A systematic structure analysis has been reported of these surfaces using LEED and STM. [52][53][54]71 The structure and the stabilization mechanism of the clean surfaces were investigated on the basis of the bulk structure of i-Cd-Yb, the parent QC of i-Ag-In-Yb. Note that i-Ag-In-Yb is isostructural to i-Cd-Yb whose bulk structure is well understood, as mentioned in Section 2.…”
Section: I-ag-in-ybmentioning
confidence: 99%
“…As such, the structure of the 2fold iAgInYb surface is characterized by a rowstructure formed of atomic bands which appear along one of the 2fold axes. 27) Recent work showed that the Ag/In and Yb atoms produce different contrast in STM at different bias polarities. 28) In this paper, the growth of Pn on the 2fold surface of the (i)AgInYb is studied by STM.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with observations on the Ag-In-Yb quasicrystal. All three high-symmetry surfaces (two-, three-, and fivefold) of this system are found to be terminated at a bulk plane containing In as the majority constituent [21][22][23]. We also present the density and composition of the surface region, including subsurface layers in Table III.…”
Section: Discussionmentioning
confidence: 97%